Comparison of Methodologies: Analytical Hierarchy Process and Grey Clustering with Entropy Weight for the Multicriteria Assessment of the Energy Sources of Perú - Sacasqui M. (2018)
This work was supported by the Consejo Nacional de Ciencia Tecnología e Innovación Tecnológica (CONCYTEC) y el Fondo Nacional De Desarrollo Científico, Tecnológico Y De Innovación Tecnológica (FONDECYT)